Financial integration in emerging market economies - Gurnain Kaur Pasricha (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
This paper analyzes de-facto integration in some Emerging Market Economies based on behavior of deviations from Covered Interest Parity in the last decade. An Asymmetric Self Exciting Threshold Autoregressive model is used to estimate bands of speculative inaction. The estimated bands follow the pattern expected, and reveal a rational market in the sense that deviations from parity are self correcting. The paper uses information from the estimated models to construct a new index of de-facto integration. Such a price-based measure of integration is crucial to studies of effectiveness of controls and of impact of capital openness on macroeconomic variables.
Keywords: F3; G1; 330; covered interest parity; threshold autoregression; financial integration index; emerging markets; de-facto openness; Finanzmarkt; Aufstrebende Märkte; Marktintegration; Zinsparität; Kapitalmobilität; Transaktionskosten; Schwellenländer